The Effect of Multicultural Experience in Conflicts Management Styles: Mediation of Cultural Intelligence and Self-monitoring - Gonçalves, Gabriela; Reis, Marta; Sousa, Cátia; Santos, Joana; Orgambídez-Ramos, Alejandro (Journal of Tourism, Sustainability and Well-being, 2015)
Conflict is an inevitable reality both in personal and in organizational life. For being inevitable, the conflict must be managed Defined as a process that occurs when one party feels adversely affected by another (e.g., De Dreu, 1997 the conflict management styles can be analysed as a function of personality variables. In this respect the cultural intelligence, self-monitoring and self-interdependent seem to be relevant variables, since characterised by flexibility and interest in other aspects present in conflict management styles. In this study, we propose that cultural intelligence, associated with the self-interdependent and self-monitoring, can have a positive impact on the choice of most effective interpersonal conflict resolution styles. Being cultural intelligence an attribute of extreme importance, we still sought to determine how the quantity and quality of intercultural contact and self-interdependent present themselves as predictors of it. With a sample of 399 individuals, the proposed model suggests that high levels of cultural intelligence mediated by a high self-monitoring and selfinterdependent positively affect and predict the conflict resolution styles adopted. Given the need to develop abilities aimed at increasing the skills of conflict resolution, this study adds to the existing literature new predictors, contributing to the welfare and performance of human resources, and consequently to success and organizational effectiveness.